1931 Fla. Laws 2069, § 7 - (:unkn) unknown (General Publisher, 1931)
Granted the Village the authority to license, tax, regulate, and prohibit explosives, guns, pistol, and other weapons.
--
Keywords: TAXATION AND LICENSURE